AMI, an Indazole Derivative, Improves Parkinson’s Disease by Inhibiting Tau Phosphorylation - Mao, Zhang; Wen-ting, Zhu; Hai-tao, Wang; Hui, Yu; Shi-yi, Lan; Jiang-ping, Xu; Wen-ya, Wang (Frontiers in Molecular Neuroscience, 2020)
Dopaminergic neurons loss is the main pathological character of Parkinson's Disease (PD). Abnormal Tau hyperphosphorylation will lead to Dopaminergic neurons loss, An indazole derivatives 6-amino-1-methyl-indazole(AMI) was successfully synthesized inhibited Tau hyperphosphorylation may exert neuroprotective effect.. The in vitro study showed that AMI effectively increased the cell viability and alleviated the apoptosis induced by MPP+ in SH-SY5Y cells. In addition, AMI treatment significantly decreased the expression of p-Tau and upstream kinases GSK3β. In the MPTP-induced PD mice models, we found AMI significantly preserved dopaminergic neurons in the substantia nigra and improved the PD behavioral symptoms. In summary, our results demonstrate that AMI exerts neuroprotective effect via inhibiting Tau hyperphosphorylation, thus represents a promising new candidate for PD treatment.